The magnitude of nephron number reduction mediates intrauterine growth-restriction-induced long term chronic renal disease in the rat. A comparative study in two experimental models. Issue 1 (December 2016) - Boubred, Farid; Daniel, Laurent; Buffat, Christophe; Tsimaratos, Michel; Oliver, Charles; Lelièvre-Pégorier, Martine; Simeoni, Umberto
Abstract Background Intrauterine growth restriction (IUGR) is a risk factor for hypertension (HT) and chronic renal disease (CRD). A reduction in the nephron number is proposed to be the underlying mechanism; however, the mechanism is debated. The aim of this study was to demonstrate that IUGR-induced HT and CRD are linked to the magnitude of nephron number reduction, independently on its cause. Methods Systolic blood pressure (SBP), glomerular filtration rate (GFR), proteinuria, nephron number, and glomerular sclerosis were compared between IUGR offspring prenatally exposed to a maternal low-protein diet (9% casein; LPD offspring) or maternal administration of betamethasone (from E17 to E19; BET offspring) and offspring with a normal birth weight (NBW offspring). Results Both prenatal interventions led to IUGR and a similar reduction in birth weight. In comparison to NBW offspring, BET offspring had a severe nephron deficit (−50% in males and −40% in females, p < 0.01), an impaired GFR (−33%, p < 0.05), and HT (SBP+ 17 mmHg, p < 0.05). Glomerular sclerosis was more than twofold higher in BET offspring than in NBW offspring (p < 0.05). Long-term SBP, GFR, and glomerular sclerosis were unchanged in LPD offspring while the nephron number was moderately reduced only in males (−28% vs. NBW offspring, p < 0.05). Conclusion In this study, the magnitude of nephron number reduction influences long term renal disease in IUGR offspring: a moderate nephron number is an insufficient factor. Extremely long-term follow-up of adults prenatally exposed to glucocorticoids are required.